The Europa world of learning - Gladman , Anthony; Routledge (Firm) ([London?] : Routledge, Taylor & Francis Group, 2009)
Directory with profiles of learned societies, museums, libraries, research institutions, and universities worldwide, including names, principal personnel, activities and publications, addresses, etc.
Title from home page (viewed Aug. 23, 2010).
Mode of access: World Wide Web.
Keywords: Learned institutions and societies -- Directories; Universities and colleges -- Directories; Education, Higher -- Directories; Academies and institutes -- Directories; Societies -- Directories; Universities -- Directories; Learned institutions and societies -- Directories; Universities and colleges -- Directories; Education, Higher -- Directories; Education -- universities -- academies